The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1038/jp.2008.111
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of sterile water by gavage drip in the fluid management of extremely low birth weight infants

Abstract: Objective: To determine whether extremely low birth weight infants who receive enteral sterile water have a reduction in treated patent ductus arteriosus or death by 28 days compared to infants with routine management.Study Design: A total of 214 infants were enrolled and randomized by 36 h of age to receive up to 50 ml kg À1 per day of enteral sterile water (n ¼ 109) for 7 days or routine fluid management (n ¼ 104). Patent ductus arteriosus treatment was defined as either indomethacin treatment or surgical li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…On average, the WHO sample children were taller than the CDC sample children 10. Both Japanese breastfed children and Japanese growth charts children were shorter than the WHO growth standards children 18.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…On average, the WHO sample children were taller than the CDC sample children 10. Both Japanese breastfed children and Japanese growth charts children were shorter than the WHO growth standards children 18.…”
Section: Discussionmentioning
confidence: 84%
“…When the WHO weight-for-age curves were compared with the Centers for Disease Control and Prevention (CDC) ones, the median weight was greater for the CDC samples than for the WHO samples except during the first 6 months 10. Overall, the CDC sample children are heavier than the WHO sample children, which implies that the prevalence of underweight (<−2 SD) would be higher when using the CDC charts than when using the WHO charts.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A randomised controlled trial in Nepal found that children 6-8 years old whose mothers received vitamin A, iron, zinc and folic acid supplements during pregnancy from~11 weeks of gestation had significantly greater height, smaller triceps skinfold thickness, subscapular skinfold thickness and arm fat area than those in the control group whose mothers were receiving vitamin A only. However, groups receiving folate alone, folate plus iron or a multiple micronutrient supplement (with the same amount of iron, zinc and folate) did not show similar results (Stewart et al 2009). A longitudinal cohort in India investigated the association between vitamin B 12 and folate status in pregnant women at 18 weeks and 28 weeks of gestation and adiposity and insulin resistance of their children at 6 years of age (Yajnik et al 2008).…”
Section: Micronutrient Intake During Pregnancy and Obesity In Later Lifementioning
confidence: 93%
“…However, groups receiving folate alone, folate plus iron or a multiple micronutrient supplement (with the same amount of iron, zinc and folate) did not show similar results (Stewart et al . ). A longitudinal cohort in India investigated the association between vitamin B 12 and folate status in pregnant women at 18 weeks and 28 weeks of gestation and adiposity and insulin resistance of their children at 6 years of age (Yajnik et al .…”
Section: Prenatal Nutrition and Obesity In Later Lifementioning
confidence: 97%